2011
DOI: 10.1108/03090591111160779
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of intrapreneurship in the Iranian agricultural extension organization

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…The Hornsby et al (2002) Hornsby et al 2013;Karimi et al 2011;Kuratko & Audretsch 2013;Marzban, Seyed & Ramezan 2013;Nikolov & Urban 2013). This specific measure forms the focus of this research.…”
Section: Objectivesmentioning
confidence: 99%
“…The Hornsby et al (2002) Hornsby et al 2013;Karimi et al 2011;Kuratko & Audretsch 2013;Marzban, Seyed & Ramezan 2013;Nikolov & Urban 2013). This specific measure forms the focus of this research.…”
Section: Objectivesmentioning
confidence: 99%
“…In the literature, entrepreneurship is mostly associated with innovativeness (Covin & Slevin 1991;Knight, 1997;Zahra, 1995). Karimi et al (2011) expressed entrepreneurship as forming new products, services, processes, technologies, and work models and emphasizing the developments in technology. Brenkert (2009) also defines innovation as the fact that firm supports new thoughts aiming to develop new product and service and encourages creative processes.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the organization, there are five factors which conducive to intrapreneurship as communication openness, control mechanisms, environmental scanning intensity, organizational management support and organizational values were the manifestation from the literature (Antoncic, 2007). Karimi, Malekmohamadi, Daryani and Rezvanfar (2011) When compare these two researches, basically those are the factors that enforce the organizations to apply corporate entrepreneurship internally and it implies the management support for create an environment that enhance corporate entrepreneurship practices in organizations.…”
Section: Definitionsmentioning
confidence: 99%
“…The relationship between corporate entrepreneurship and organizational performance had been discussed in the literature by different researchers by using different samples i.e. from different organizational settings (Zahra, 1995;Karimi et al, 2011) and different countries (Antoncic, 2007;Zain and Hassan, 2007;Aktan and Bulut, 2008;Ozdemirci, 2011;Yang, Li-Hua, Zhang, and Wang, 2007;Wang and Zhang, 2009;Felicio, Rodrigues and Caldeirinha, 2012). Zahra (1995), in his study showed the changes in a company's entrepreneurial activities which impact its performance based on the sample of leveraged buyout firms.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation